‘To be on the safe side’: a qualitative study regarding users’ beliefs and experiences of internet-based self-sampling for Chlamydia trachomatis and Neisseria gonorrhoeae testing - Björn Herrmann (BMJ Publishing Group, 2020)
Objectives In Sweden, an increasing number of tests for sexually transmitted infections are conducted. Self-sampling services are provided free of charge at the national eHealth website. Our aim was to obtain a deeper understanding of users’ beliefs and experiences of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) self-sampling services.Methods This qualitative study is part of the national project ‘Internet-based chlamydia and gonorrhoea self-sampling test’, conducted in Sweden. Individuals ordering a CT/NG self-sampling test at home from the eHealth website were invited to participate. Of the 114 individuals who agreed, a purposeful sample including 20 women and men aged 18–49 years (mean, 30.8 years) participated in a telephone interview in 2019.Results The test service for CT/NG was highly appreciated by men and women of different ages. Round-the-clock accessibility, avoiding clinical visits, ease of use, confidentiality and a rapid test result were reasons for this appreciation. Language, uncertainty about the correct sampling procedure, unreliable postal services and concerns about handling of personal data were mentioned as barriers. Reasons for testing were checking after unprotected sex, symptoms, checking a partner’s fidelity or a regular routine—‘to be on the safe side’. Knowledge about the infections and their consequences was limited; some considered them severe, especially if they could threaten fertility, and others were less concerned. Disclosing an infection was described as emotionally stressful. Participants had high self-efficacy in relation to the test and would not hesitate to use the service again, even if it involved a cost.Conclusions Internet-based CT/NG self-sampling at home was highly appreciated and was used for individual health reasons, but also out of concern for others’ health and for society as a whole. The benefits seem to outweigh the barriers, and the service may therefore continue to be widely offered.